Effectiveness of Kegel Exercise Combined With Utkatasana on Symptoms Associated With Stress Urinary Incontinence On Middle Aged Women: Life Sciences-Health - T, Murugaraj; Ashila; Hariharan, Sabarish; A, Mossadeq; E, Shanmugananth (International Journal of Life Science and Pharma Research, 2022)
Millions of women are affected by Stress Urinary Incontinence (SUI). Here stress urinary incontinence refers to physical pressure rather than mental stress. SUI is one of the most common types of urinary incontinence. Kegel exercise and Utkatasana treats SUI symptoms by reinforcing weakened pelvic floor muscle and improving elasticity. But there was no evidence found that Kegel exercise combined with Utkatasana on symptoms associated with stress incontinence. so, the purpose of the study is to find out the effects of Kegel exercise and Kegel exercise combined with Utkatasana for symptoms associated with Stress Urinary Incontinence. This is a quasi-experimental study, 20 samples diagnosed with stress urinary incontinence referred from the department of urology of a tertiary care institution, aged between 25-50 years, who were willing were included in this study. Subjects having gynecological problems, neurological disorders, diabetes mellitus were excluded from this study. The subjects were evaluated and accessed before the beginning of the exercise session using unipolar scale questionnaire. Samples were divided into two groups A and B, Group A subjects received Kegel exercise alone and Group B subjects received Kegel exercise along with Utkatasana for a period of 3 months. The Pre and Post values were documented by using a unipolar scale questionnaire. Data are interpreted with the help of an Incontinence quality of life questionnaire (schurch). The data was analyzed under 3 domains namely Avoidance and Limiting Behaviour(ALB), Psycho-Social Impacts(PSI), and Social Embarrassment (SE). The data obtained from both Group A & Group B were documented and analyzed. Based on the statistical analysis it is found that the subjects in Group B showed marked improvement in Avoidance and Limiting Behaviour (ALB), Psycho-Social Impacts (PSI), and Social Embarrassment(SE) than those from the subjects of Group A Statistics were estimated for all 22 items and for the 3 domains of the I-QOL.: According to the results Kegel exercise combined with Utkatasana was found to be an effective treatment than the Kegel treatment alone for symptoms associated with SUI.